Idiomatic Expression Found in Movie Script of The Beauty and The Beast : A Semantics Study - Ilmi Fadillah; Puspita Sari (Universitas Cokroaminoto Palopo, 2022)
The purpose of this study is to identify the types of idiomatic expressions in the script of the movie